Prognostic significance of p21WAF1/CIP1, p27Kip1, p53 and E-cadherin expression in gastric cancer. Issue 7 (4th May 2007) - Gamboa-Dominguez, Armando; Seidl, Stefan; Reyes-Gutierrez, Edgardo; Hermannstädter, Christine; Quintanilla-Martinez, Leticia; Busch, Raymonde; Höfler, Heinz; Fend, Falko; Luber, Birgit
Abstract : Background: Gastric carcinoma is characterised by numerous genetic and epigenetic alterations that influence cell cycle progression, apoptosis and DNA repair. These alterations include down-regulation of the cyclin-dependent kinase (CDK) inhibitors p21 WAF1/CIP1 and p27 Kip1, and mutations of the tumour suppressor protein p53 and the cell adhesion molecule E-cadherin. Combined evaluation of the prognostic significance of these alterations has not been reported in Mexican Mestizo patients. Aims: To evaluate p21 WAF1/CIP1, p27 Kip1, p53 and E-cadherin protein expression, including mutant E-cadherin variants with deletion of exon 8 ( del 8 ) or 9 ( del 9 ), in gastric cancer from Mexican patients. Methods: Immunohistochemistry for the above-mentioned markers, including mutation-specific E-cadherin antibodies, was carried out in 69 gastric carcinomas; expression levels were correlated with histotype, tumour stage and prognosis. Results: Expression of p21 WAF1/CIP1 alone or in combination with p27 Kip1 or in the absence of p53 was associated with favourable prognosis. Staining of del 8 and del 9 E-cadherin was found exclusively in patients negative for p53 and positive for p21 WAF1/CIP1, suggesting that the p21 WAF1/CIP1 regulatory function of p53 was intact. Conclusion: Combined evaluation of the prognostic significance of cell cycle regulators and E-cadherin should be performed. Even though patients negative for p53 and positive for p21 WAF1/CIP1 have a favourable prognosis, it may have a negative influence on prognosis if they acquire in addition E-cadherin mutations which have been shown previously to be associated with poor survival.